Media engagement in the transnational social field: discourses and repositionings on migration in the Romanian public sphere. - Beciu, Camelia; Mădroane, Irina Diana; Ciocea, Mălina; Cârlan, Alexandru I. (Critical Discourse Studies, 2017)
The article examines the construction of transnational migrant agency in the media of the sending country, starting from the contestation and reinterpretation in the Romanian press of a British documentary about Romanian migrants in the UK. It proposes an analytical framework that allows insights into the ways in which the national mainstream media engage in transnational dynamics. The findings show that Romanian journalists construct a European field of power relations where Romania is in a disadvantageous position, followed by a symbolic appropriation of the migrants’ identities, as a means of rearticulating the country’s position in this field. This is coupled with the emergence of a self-reflexive discourse that informs a stance of collective responsibility and provides well-grounded reasons for a debate about ‘us’. The Romanian media (re)produce a politics of belonging, legitimising particular migrant–non-migrant relationships as well as policies, and (re)position themselves and their publics towards the issue of intra-EU migration.